Pharmacoinformatics-based strategy in designing and profiling of some Pyrazole analogues as novel hepatitis C virus inhibitors with pharmacokinetic analysis. Issue 1 (31st December 2023) - Ejeh, Stephen; Uzairu, Adamu; Shallangwa, Gideon A.; Abechi, Stephen E.; Ibrahim, Muhammad Tukur
ABSTRACT: Hepatitis C virus (HCV) infection promotes death rates all over the world. Sofosbuvir is a standard drug for the cure of HCV but unfortunately, it receives a lot of attention for its pricing problems. As a result, it is crucial to consider alternative HCV treatments that are both cost-effective and free of side effects. We report how a pharmacoinformatics-based technique was used to generate and profile certain Pyrazole analogues as novel hepatitis C virus inhibitors by exploring the PubChem drug repository for the lead molecule with further optimization. The proposed molecules all interact by filling the protein target's binding domain to inhibit the receptor. With binding energy of −35.72 kcal/mol, compound 17e was found as a highly potent NS5B inhibitor, exceeding Sofosbuvir, the FDA-approved NS5B inhibitor with a binding energy of −30.34 kcal/mol. Additionally, the ADMET assessment of the selected molecules (17e) shows outstanding quality with a drug score of 0.74 when especially in comparison to Sofosbuvir, which has a drug score of 0.31. Future studies should therefore focus on the molecular dynamics, synthesis, in vivo testing, and in vitro evaluation of these substances to validate our hypothesis.